Experimental in-plane behaviour and drift-based fragility assessment of typical Peruvian confined masonry walls - Tarque, N.; Alfredo, M.; Lovon, L.; Marcial, B.; Varum, V. (Elsevier, 2022)
Around 56% of dwellings in Lima are constructed with confined masonry walls, and over 70% are built without engineering design and supervision. This building stock is exposed to the seismic activity of the Peruvian coastline. Then, in case of a severe earthquake, many of these buildings may suffer significant damage and eventually collapse, causing high economic losses and fatalities. Thus, it is essential to investigate the seismic behaviour of these constructions to understand their seismic vulnerability. This work studied the seismic performance of typically confined masonry walls built with hollow bricks based on cyclic in-plane tests. The imposed boundary conditions allowed the walls to behave as a cantilever. The influence of vertical pre-compression was also explored by performing separate tests with and without such load. Outcomes suggest that these walls may collapse after 0.5% drift. Also, mechanical features like stiffness degradation and damping values were calculated for different displacement limit states. Finally, fragility curves of confined masonry walls considering different unit types (i.e. solid, hollows, tubular), axial load ratio, and horizontal reinforcement are computed. The results demonstrate that tubular units should be forbidden as bearing walls, and horizontal reinforcement inside the walls improves their displacement ductility.
Keywords: Confined Masonry (CM); Seismic Gap (Lima); Informal Construction; https://purl.org/pe-repo/ocde/ford#2.01.01